2021
DOI: 10.1159/000520568
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Home-Use versus Office-Use Diphenylcyclopropenone in Extensive Alopecia Areata

Abstract: <b><i>Introduction:</i></b> Diphenylcyclopropenone (DPCP) is the medication of choice for the treatment of severe alopecia areata (AA) according to AA treatment guidelines. Precise initiation and application are important factors for successful treatment. However, it is difficult for patients who live far away to visit their doctor weekly. <b><i>Methods:</i></b> We conducted a retrospective cohort study to assess the cost, effectiveness, and side effects of DPCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this study, as in the most studies, cases treated with a dosage of 5 mg twice a day of tofacitinib were followed after 6 month 18,28,29 . The average maintenance dose of the drug in our study was 7 mg daily, which reduced the risk of any side effects caused by increasing the dose of the drug.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, as in the most studies, cases treated with a dosage of 5 mg twice a day of tofacitinib were followed after 6 month 18,28,29 . The average maintenance dose of the drug in our study was 7 mg daily, which reduced the risk of any side effects caused by increasing the dose of the drug.…”
Section: Discussionmentioning
confidence: 84%
“…Most of the annual cost burden of DPC treatment was due to staff time and overhead rather than the cost of the DPC itself: $258 for the DPC, $978 in staff time and overhead for the department, and $1233 directly charged to the patient. 21 Lekhavat et al 22 studied the economic impact of home-use vs office-use DPC in extensive AA (N=82). Both groups received weekly treatments in the hospital until DPC concentrations had been adjusted.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 99%
“…There was no significant difference between groups in the proportion of patients who responded favorably to the DPC. 22 JAK Inhibitors-Chen et al 23 studied the efficacy of low-dose (5 mg) tofacitinib to treat severe AA (N=6). Compared to prior studies, [24][25][26][27] this analysis reported the efficacy of low-dose tofacitinib was not inferior to higher doses (10-20 mg), and low-dose tofacitinib reduced treatment costs by more than 50%.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, only a few retrospective studies have been published on the effectiveness and safety of home-based contact immunotherapy. [4][5][6][7] This study included the largest number of AA patients, including children, and further evaluated the convenience and economic burden as well as the efficacy and safety of home-based DPCP-immunotherapy.…”
mentioning
confidence: 99%